Transitioning towards a New International Economic Order: Risks on the Road - Saez Contreras, Sebastian (Latin American Journal of Trade Policy, 2024)
The international economic order that has governed us for more than 30 years is changing. The globalization that characterized the international economy at the end of the twentieth century and the beginning of the present is being threatened by potential setbacks in the process of globalization, greater protectionist pressures, and an increase in tensions between the main economic powers. We find ourselves in a situation of insecurity and risks of international conflicts unprecedented since the end of the Second World War: cooperation, dialogue, and coexistence between countries is at risk. The central hypothesis of this paper is that we are in a transition towards a new international economic order. The paper examines the foundations and importance of the international economic order, its main milestones and institutions, its main results and the reasons for its weakening. Finally, the possible consequences of these developments are examined.